Case Report: A Rare Case of Esophagogastric Junctional Squamous Cell Carcinoma After the Successful Treatment of Neuroendocrine Carcinoma: Clonal Tumor Evolution Revealed by Genetic Analysis - Sato, Hiroki; Saito, Takeshi; Horii, Hiroshi; Kajiura, Mami; Kikuchi, Noriaki; Takada, Nobuhisa; Taguchi, Koichi; Yoshida, Mika; Hasegawa, Masakazu; Taguchi, Hiroyuki; Yoshida, Yukinori; Ando, Katsuyoshi; et al. (Frontiers in Genetics, 2021)
Neuroendocrine carcinoma (NEC) of the esophagogastric junction (EGJ) is a rare disease with no established treatments. Herein, we describe a case of recurrent squamous cell carcinoma (SCC) after achieving complete response to chemotherapy against NEC of the EGJ. A 67-year-old man was referred to our hospital because of epigastric discomfort. Computed tomography imaging and esophagogastroduodenoscopy revealed ulcerated tumors at the EGJ. Endoscopic biopsy revealed small tumor cells with a high nuclear/cytoplasmic ratio, suggesting small-cell NEC. Immunohistochemistry (IHC) analysis showed tumor cells with an MIB-1 index of 80%. The patient achieved complete response after 10 cycles of chemotherapy. Follow-up endoscopic examination revealed small red-colored mucosal lesions in the center of the cicatrized primary lesion. Re-biopsy detected cancer cells harboring large eosinophilic cytoplasm with keratinization and no evidence of NEC components. IHC of the cells were cytokeratin 5/6-positive and p53-negative. The tumor persisted without evidence of metastases after chemoradiotherapy, and total gastrectomy with lymph node dissection was performed. Pathological assessment of the resected specimens revealed SCC, without evidence of NEC. The patient survived without a recurrence for >3 years after the initial presentation. Somatic mutation profiles of the primary NEC and recurrent SCC were analyzed by targeted amplicon sequencing covering common cancer-related mutations. Both tumors possessed TP53 Q192X mutation, whereas SMAD4 S517T was found only in SCC, suggesting that both tumor components originated from a founder clone with a stop-gain mutation in TP53. The somatic mutation profile of the tumors indicated that that loss of heterozygosity (LOH) at the TP53 gene might have occurred during the differentiation of the founder clone into NEC, while a SMAD4 mutation might have contributed to SCC development, indicating branching and subclonal evolution from common founder clone to both NEC and SCC. The mutation assessments provided valuable information to better understand the clonal evolution of metachronous cancers.